2019
DOI: 10.3847/1538-4357/ab385c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatially Resolved V−3.6 μm Colors and Dust Extinction in 257 Nearby NGC and IC Galaxies

Abstract: We present and analyze spatially-resolved maps for the observed V -and g-band to 3.6 µm flux ratios and the inferred dust extinction values, A V , for a sample of 257 nearby NGC and IC galaxies. Flux ratio maps are constructed using PSF-matched mosaics of SDSS gand r-band images and Spitzer/IRAC 3.6 µm mosaics, with all pixels contaminated by foreground stars or background objects masked out. By applying the β V method (Tamura et al. 2009(Tamura et al. , 2010, which was recently calibrated as a function of red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Before being interpreted as star formation indicators, both rest-UV and Hα emission need to be corrected for attenuation due to the presence of dust in the host galaxy itself. Since the main goal of this work is to compare the rest-UV and Hα emission from galaxies as a function of their positions inside the galaxy, it is imperative to make an effort to address the fact that dust absorption may itself vary inside a galaxy (e.g., Kim et al 2019). Hence, we compute a resolved dust map for each galaxy to correct for dust attenuation, while preserving the morphological detail.…”
Section: Correcting For Dustmentioning
confidence: 99%
“…Before being interpreted as star formation indicators, both rest-UV and Hα emission need to be corrected for attenuation due to the presence of dust in the host galaxy itself. Since the main goal of this work is to compare the rest-UV and Hα emission from galaxies as a function of their positions inside the galaxy, it is imperative to make an effort to address the fact that dust absorption may itself vary inside a galaxy (e.g., Kim et al 2019). Hence, we compute a resolved dust map for each galaxy to correct for dust attenuation, while preserving the morphological detail.…”
Section: Correcting For Dustmentioning
confidence: 99%
“…Bonatto et al (2013) found extinction in 66 GCs with mean values ranging from 〈δE(B − v) 〉 ≈ 0.018 (NGC 6981) to 〈δE(B − v) 〉 ≈ 0.016 (Palomar 2), and therefore an implied A V ∼ 0.05 mag, consistent with the above value. More recent work by Kim et al (2019) made a pixel-to-pixel analysis of a large sample of nearby ellipticals with ground-based and Spitzer 3.6 μm images and found that the radial extinction profiles in the elliptical centers have on average A V  0.1 mag and generally do not exceed A V = 0.2 mag in their central reddening values.…”
Section: The Color-magnitude Datamentioning
confidence: 99%